To see and to make people see precariousness and social revolt : based on the work of Nathalie Quintane (Altre Modernità, 2025)
In some of her writings, Nathalie Quintane gives a decisive place to a conception of the event as that which disrupts the conceptual and linguistic categories in use, and commits the writer to finding new forms in order to be described. In some of her recent works, notably Un œil en moins (2018, in which she recounts a year of militant action, marked by the « Nuit Debout » movement) and Les Enfants vont bien (2019, which evokes the fate of migrants in France today), she poses a central question: how can we look differently, in order to see what we refuse to see (in this case, the violence done by the state to women and men in France today). For Quintane, it all comes down to an effort of formulation, a work of language that must bring certain realities into a different kind of visibility. It's a singular « politics of literature », built around the notion of attention, that emerges in her texts.
Keywords: French literature; contemporary; literature and politics; attention; Nathalie Quintane